2018
DOI: 10.1007/s00011-018-1146-7
|View full text |Cite
|
Sign up to set email alerts
|

Genistein modulates the expression of Toll-like receptors in experimental autoimmune encephalomyelitis

Abstract: These findings shed light on the potential of genistein as a prophylactic strategy for multiple sclerosis (MS) prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…On the other hand, although some TLRs have been shown to have detrimental effects in brain inflammation, other studies have reported that pattern recognition receptors, such as TLR3 can have important functions in ameliorating the progression of MS (Marta, 2009). In the EAE mouse model, TLR3 and TLR9 responses were found to be downregulated (Marta, 2009), and an activator of TLR3 rescued cellular infiltration in neuronal tissue and reduced demyelination (Evangelista et al, 2016; Dias et al, 2018). Interestingly, TLR3 has gained special attention because of its role in the control of HSV-1 infection of the CNS.…”
Section: Cns Inflammation Induced By Hsv-1mentioning
confidence: 99%
“…On the other hand, although some TLRs have been shown to have detrimental effects in brain inflammation, other studies have reported that pattern recognition receptors, such as TLR3 can have important functions in ameliorating the progression of MS (Marta, 2009). In the EAE mouse model, TLR3 and TLR9 responses were found to be downregulated (Marta, 2009), and an activator of TLR3 rescued cellular infiltration in neuronal tissue and reduced demyelination (Evangelista et al, 2016; Dias et al, 2018). Interestingly, TLR3 has gained special attention because of its role in the control of HSV-1 infection of the CNS.…”
Section: Cns Inflammation Induced By Hsv-1mentioning
confidence: 99%
“…It has been found that prophylactic oral treatment with Gen is capable to modulate the immune response and reduce the EAE severity, if initiated in the early stages of the disease, through increasing the expression of Toll‐like receptors (TLR3, TLR9) in dendritic cells and macrophages, and endogenous IFN‐β production in the spinal cord. These activate suppressor T‐cells and inhibit IL‐17 and IL‐23 production besides reducing the factors of Th1 and Th17 cells (Dias et al, 2018) (Figure 7). These findings support the previous outcomes obtained by Jahromi, Arrefhosseini, Ghaemi, Alizadeh, Sabetghadam, and Togha (2014) who reported that treating C57Bl/6 mice models of EAE with Gen reduced neuronal demyelination, suppressed the production of IFN‐γ and enhanced IL‐10 secretion in the brain during the early phases of the disease.…”
Section: Molecular Targets Of Phytoestrogen‐isoflavones In Neurodegen...mentioning
confidence: 99%
“…98 IFN-β has a vital role in treating MS by decreasing the frequency of the relapses and the appearance of novel lesions. 99 Dias et al have demonstrated the genistein ability to moderate the involved factors in innate immune response in the EAE preliminary phase. The therapy with genistein delayed the disease resumption, with decreased inflammatory demyelination as well as infiltration.…”
Section: Animal Studiesmentioning
confidence: 99%
“…This study may show the genistein potential as a preventative strategy for preventing multiple sclerosis (MS). 99 Ohgomori et al figured out that GEN could act on mature oligodendrocytes in the hippocampus by increasing their myelin formation and survival and offer the phytoestrogens therapeutic possibility to treat MS patients who suffer from mental health problems. 100…”
Section: Animal Studiesmentioning
confidence: 99%